Students' evaluation of teaching in the project-based learning programme: An instrument and a development process. Issue 2 (July 2021) - Pan, Gary; Shankararaman, Venky; Koh, Kevin; Gan, Sandy
Abstract: Students' evaluation of teaching (SET) is widely adopted in most universities. Besides allowing teachers to improve their teaching, SET offers an important input for university administrators' consideration in faculty promotion, contract renewal, salary increase and teaching award. While the practice of using SET instrument is well established, it remains ambiguous in the SET literature whether a dedicated SET instrument is used for alternative teaching pedagogy. Our paper argues that SET instrument may need to be re-designed to reflect the idiosyncrasy of another teaching pedagogy. Accordingly, this paper presents the development process of a SET instrument used to measure an alternative teaching pedagogy in project-based learning. By drawing upon a case study of a university in Singapore, we demonstrate the development of a SET instrument and highlight the considerations surfaced during the development process. Our findings showed that active involvement of students and faculty in the development process proved to be important for the successful development and implementation of SET instrument. The paper concludes with implications for research and education, and limitation of this study. Highlights: Develop a dedicated student evaluation of teaching instrument to measure the idiosyncrasy of project-based learning pedagogy. Consider the perspectives raised by students and faculty in the development of a student evaluation of teaching instrument. Send multiple reminders to students and emphasize on student confidentiality may encourage participation in students' evaluation of teaching instrument.